2010
DOI: 10.1021/bi100973m
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Regulatory Segment of Poly(ADP-ribose) Glycohydrolase

Abstract: Coordinate regulation of PARPs-1/2 and PARG is required for cellular responses to genotoxic stress. While PARPs-1/2 are regulated by DNA breaks and covalent modifications, mechanisms of PARG regulation are poorly understood. We report here discovery of a PARG regulatory segment far removed linearly from residues involved in catalysis. Expression and analysis of human PARG segments identified a minimal catalytically active C-terminal PARG (hPARG59) containing a 16-residue N-terminal mitochondrial targeting sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 44 publications
3
42
0
Order By: Relevance
“…This isoform completely lacks exon 4 (and thus, the MTS) as well as a substantial amount of exon 5-encoded amino acids, whose importance for efficient PAR-degradation was demonstrated in this study. Indeed, lack of PARdegrading activity was shown for an N-terminally truncated human PARG isoform that would reflect mPARG52 with regard to translational initiation and exon composition (43). Taken together, these findings suggest that the mammalian PARG gene encodes cytosolic and mitochondrial isoforms that do not display PAR-degrading activity.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This isoform completely lacks exon 4 (and thus, the MTS) as well as a substantial amount of exon 5-encoded amino acids, whose importance for efficient PAR-degradation was demonstrated in this study. Indeed, lack of PARdegrading activity was shown for an N-terminally truncated human PARG isoform that would reflect mPARG52 with regard to translational initiation and exon composition (43). Taken together, these findings suggest that the mammalian PARG gene encodes cytosolic and mitochondrial isoforms that do not display PAR-degrading activity.…”
Section: Discussionmentioning
confidence: 92%
“…These findings extend the critical role of amino acids within the MTS for catalysis (43) by the adjacent amino acids encoded by exon 5. Amino acid exchanges within the MTS affected the catalytic activity of PARG55(ex5) as well as of N-terminally extended PARG variants (43). However, the MTS is part of the primary structures of both PARG55 and PARG60, and deletion of the MTS caused PARG55(ex5) to become inactive.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the N-terminal accessory domain of the TTPARG accounts for approximately half of the enzyme structure and is predominantly α-helical in nature, with the exception of a few β-strands that form an extension to Supplementary Fig. S4), demonstrating that the RS/MTS motif 14 and a large part of the N-terminal domain are not absolutely essential for the enzymatic activity of canonical PARGs.…”
Section: Resultsmentioning
confidence: 99%
“…Despite this progress, structural information on the canonical PARGs is still lacking. Recent studies identified a minimal region in human PARG required for catalytic activity in vitro, which extends beyond the macrodomain alone 14 . This amino-terminal extension contains a short motif called the Regulatory Segment/MTS (RS/MTS) that was suggested to be essential for PARG activity 14 .…”
mentioning
confidence: 99%
See 1 more Smart Citation